Modern Study Table for Small Houses Inspired by Origami - Chan, Jun Hao; Selimin, Mohamad Ali; Sidek, Ahmad Anwar Safwan (Research in Management of Technology and Business, 2022)
Nowadays, the newest tiny-size apartments have floorspaces as little as 10 to 15 meters square. When compared to 30 years ago, a tiny flat has gotten smaller over time. This may cause people who live in small, congested, and cluttered spaces to feel worried, imprisoned, and claustrophobic. This will indirectly increase the degree of contentment with the lodging. Therefore, the purpose of this research is to identify design criteria, design, and develop a prototype of a modern study table with multifunctional features for users who live in small size houses. This study began with an online questionnaire survey distributed via Google Form to 50 respondents in Pagoh, Johor. This obtained data was converted into design criteria for the design process. The survey yielded design criteria such as pinewood as a material, closed storage, stainless steel table legs, natural colour, and a flip-top mirror. Following that, the design process began with the drawing of 30 thumbnails, 6 ideations, and 4 concept developments. Three idea development sketches were utilized as candidates for this study's final design selection that was done via a simple survey. A new prototype of a modern study table made of rubberwood and coated with wood lacquer was successfully produced. Finally, by wisely utilising the limited space of tiny homes, this innovative design study table is able to solve the mentioned problem.